2016
DOI: 10.1016/j.cell.2016.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Hardwiring Stem Cell Communication through Tissue Structure

Abstract: Adult stem cells across diverse organs self-renew and differentiate to maintain tissue homeostasis. How stem cells receive input to preserve tissue structure and function largely relies on their communication with surrounding cellular and non-cellular elements. As such, how tissues are organized and patterned not only reflects organ function but also inherently hardwires networks of communication between stem cells and their environment to direct tissue homeostasis and injury repair. This review highlights how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 126 publications
0
83
0
Order By: Relevance
“…Additionally, hair germ cells were shown to recolonize bulge stem cells after their ablation. Using live imaging coupled with photoablation, this study elegantly demonstrated that hair germ cells could convert to bulge stem cells and then participate in hair growth [71,79]. However, again, long-term lineage tracing needs to be performed to understand whether these new bulge cells participate in recurring hair cycles.…”
Section: Cell Plasticity In Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, hair germ cells were shown to recolonize bulge stem cells after their ablation. Using live imaging coupled with photoablation, this study elegantly demonstrated that hair germ cells could convert to bulge stem cells and then participate in hair growth [71,79]. However, again, long-term lineage tracing needs to be performed to understand whether these new bulge cells participate in recurring hair cycles.…”
Section: Cell Plasticity In Mammalsmentioning
confidence: 99%
“…This phenomenon is based upon a gradient of a short-range morphogen from the hub cell which is, at least in part, the molecular basis for the hub cell niche function [23,8487]. Similarly, in hair follicles, the ability of regenerating lost bulge stem cells is dependent upon signals derived from the dermal papillae [65,71,79,83]. In the airway epithelium, the ability of mature secretory cells to dedifferentiate is actually restrained in the presence of the actual stem cells themselves [36,88].…”
Section: Restraining Plasticity: How Do Cells Maintain Their State?mentioning
confidence: 99%
“…Additionally, as basal stem cells stochastically commit to differentiation, they reuse existing structural organizations (Rompolas, Mesa, et al. , 2016; Xin et al. , 2016).…”
Section: My Lab’s Scientific Contributions and Visionmentioning
confidence: 99%
“…The skin harbors a rich array of cell types, including epidermis, hair follicles, dermal fibroblasts, and adipocytes (Blanpain and Fuchs 2009;Hsu et al 2014a;Chen et al 2016;Shook et al 2016;Xin et al 2016). Among them, hair follicles undergo cyclical rounds of growth (anagen), regression (catagen), and rest (telogen).…”
mentioning
confidence: 99%